Patchouli oil isolated from the leaves of Pogostemon cablin ameliorates ethanol-induced acute liver injury in rats via inhibition of oxidative stress and lipid accumulation. Issue 43 (5th July 2018) - Huang, Qiong-Hui; Wu, Xue; Chen, Xiao-Hong; Wu, Jia-Zhen; Su, Zi-Ren; Liang, Jia-Li; Li, Yu-Cui; Lai, Xiao-Ping; Chen, Jian-Nan; Liu, Yu-Hong
Abstract : Excessive alcohol consumption can cause serious hepatic injury which is associated with oxidative stress and fatty metabolic disturbance. Abstract : Excessive alcohol consumption can cause serious hepatic injury which is associated with oxidative stress and fatty metabolic disturbance. Patchouli oil (PO) is a sort of food supplement with high medicinal value in hepatoprotection, but its ability against ethanol-induced liver failure has not been demonstrated. Thus, this study aimed to investigate the potential hepatoprotection of PO through an ethanol-induced hepatotoxicity rat model. Our results showed that PO pretreatment could dramatically decrease the levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP) and lactate dehydrogenase (LDH) in serum, paralleled by an improvement of histopathology alterations. Additionally, PO could markedly suppress the content of reactive oxygen species (ROS), tumor necrosis factor alpha (TNF-α), free fatty acid (FFA), and triglyceride (TG), while enhancing the activities of glutathione (GSH), glutathione reductase (GR), and superoxide dismutase (SOD) as well as the ratio of glutathione to oxidized glutathione (GSH/GSSG) in liver. The protective effect of PO against oxidative stress was interrelated with restraining the mRNA and protein expression of hepatic microsomal enzyme cytochrome P450 2E1 (CYP2E1). What's more, PO pretreatment could also accelerate lipometabolism via up-regulating expressions of adenosine monophosphate-activated protein kinase (AMPK), peroxisome proliferator-activated receptor α (PPAR-α), and carnitine palmitoyltransferase 1 (CPT-1) and down-regulating expressions of nuclear factor-kappaB (NF-κB) p65, sterol regulatory element-binding protein 1 (SREBP-1c), fatty acid synthase (FAS), and stearoyl-CoA desaturase 1 (SCD-1). To conclude, PO showed potent effect against ethanol-induced hepatotoxicity by relieving oxidative stress and preventing lipid accumulation.